Substrate and Ca2+-Induced Conformational Changes in Human 15-LOX-2 - Alkins, Scott Denman (My University, 2025)
Lipoxygenases (LOXs) are a family of iron enzymes that catalyze the peroxidation of polyunsaturated fatty acids to generate oxylipins, which in animals play essential roles in signaling. Human LOXs can also contribute to inflammation; as one of the six encoded LOX enzymes, epithelial 15-lipoxygenase-2 (15-LOX-2), is involved in the pathophysiology of atherosclerosis, a common form of cardiovascular disease characterized by a buildup of plaque along the walls of arteries. While the structures of many animal LOXs, including 15-LOX-2, have been solved, questions remain unanswered in understanding the mechanism of LOX catalysis due to conformational changes that may influence its activity. Calcium is an allosteric effector of animal LOXs that induces conformational changes promoting the translocation of the LOX to the phospholipid membrane. This allosteric effector increases activity by 4-fold. Differential scanning calorimetry was used to determine that, in the presence of calcium, the transition temperature increases by 1˚C, indicating that the calcium-dependent structural change stabilizes the 15-LOX-2 structure. To further probe these conformational changes, we performed limited proteolysis experiments in both the absence and presence of lipids. Limited proteolysis of 15-LOX-2 showed no impact of lipids on degradation. However, another animal LOX, coral 11R-LOX, which requires lipids present for activity, revealed a lipid-dependent increase in digestion of the enzyme. The data support a lipid-dependent change in conformation from a closed to an open conformation. Our results strongly support that protein flexibility, which is regulated by lipids and Ca2+, is essential for controlling LOX catalysis.
Keywords: Lipoxygenase; Allosteric Effects; Limited Proteolysis; Differential Scanning Calorimetry